Stress analysis of intervertebral disc during occupational activities. (September 2021) - Jo, Minhye; Chae, Soo-Won
Highlights: l New method for the biomechanical analysis of intervertebral disc during occupational activities. l Effect of trunk flexion angles and load weight on the stresses and strains in intervertebral disc. l Initial position of hand loads further from the spine induced a greater risk of low back injury. Abstract: Background and objective: Manual material handling activities cause large compression of the intervertebral disc of the lumbar spine. Intradiscal pressure (IDP) has generally been employed to predict the risk of low back injury. As an alternative to in vivo measurements, either motion analysis or finite element (FE) analysis has been used to estimate IDP. The purpose of this study is to propose a new biomechanical method that integrates FE analysis with motion analysis, in order to estimate the stresses and deformations of the intervertebral disc of the lumbar spine during occupational activities. Methods: In the proposed method, motion analysis is performed first by using motion capture data, and the results are employed as input data to FE analysis at specific times of interest during motion. In this method, an in-house interface program is used to scale an initial reference FE model to the subject of experiment, and transformed to the corresponding posture at a specific time during motion. The muscle forces and GRF obtained from motion analysis are applied to FE analysis as boundary and loading conditions. For a total of eighteen occupational activities, the IDP, shear stress, and strain of the L4–L5 segment are estimated. Results: Under each in vivo activity, the predicted IDP was in overall agreement with the available in vivo data. For lifting activities according to lift origin position, the maximum IDP occurred in the far-knee position immediately after lifting. As the lift origin position moved away from the spine, the stresses and strains in the disc increased. Conclusions: This new proposed method is expected to allow the estimation of the stresses and deformations in the intervertebral disc during various occupational activities.